QUANTITATIVE MINERAL MATTER DETERMINATION IN LIGNITES USING X-RAY DLFRACTOMETRY AND POSITION SENSITIVE DETECTOR (XRD-PSD) - Παπαζησίμου, Σ.; Καλαϊτζίδης, Σ. (Bulletin of the Geological Society of Greece, 2004)
Thirty lignite samples from western Péloponnèse (Greece) were examined in the Department of Mineralogy, Natural History Museum, London, using an X-Ray Diffractometer equipped with a Position Sensitive Detector (Enraf-Nonius PSD 120). Diffraction patterns acquisition time was only 5 min with the minimum interference of the organic matter. Qualitative and quantitative evaluation of the mineral matter present performed using GUFI5 Enraf-Nonius software and involved a pattern-fit stripping technique. The prevailing minerals in all the studied samples are the mixed layers of illite/smectite, quartz, muscovite and K-feldspars. The weight percentages of the mineral matter as it was calculated from the diffraction patterns display high correlation coefficient (>0.85) with the respective wt.-% of ash in 750°C for most of the samples. The low correlation coefficient (0.65) of some samples may be attributed to the very small size of the mineral crystalline particles and/or the presence of inorganic amorphous phases.